Differential impact of radiation therapy after radical prostatectomy on recurrence patterns: an assessment using [68Ga]Ga-PSMA ligand PET/CT(MRI) - Grubmüller, Bernhard; Jahrreiss, Victoria; Huebner, Nicolai; Mitterhauser, Markus; Stangl-Kremser, Judith; Grubmüller, Karl Hermann; Baltzer, Pascal; Hacker, Marcus; Goldner, Gregor; Shariat, Shahrokh F; Rasul, Sazan (Prostate cancer and prostatic diseases, 2021)
PURPOSE: To evaluate the differential impact of postoperative radiotherapy (RT) on recurrence patterns in patients treated with radical prostatectomy (RP) using [68Ga]Ga-PSMAHBED-CC conjugate 11 positron emission tomography (PSMA 11-PET). METHODS: We assessed 162 consecutive patients who experienced biochemical recurrence (BCR) after RP for nonmetastatic prostate cancer (PC). All had at least one positive lesion on imaging. No patient was on androgen deprivation therapy (ADT). Patients were categorized into those who had received adjuvant/salvage RT ± ADT and those who did not (RP only). Lesion- and patient-based analyses were performed. The impact of the radiation field was assessed. RESULTS: Overall, 57 BCR patients underwent RP only, 105 received postoperative RT. Median PSA was 1.01 ng/ml (IQR 0.58-2). In the lesion-based analysis, compared to the RP only patients, those who had received postoperative RT, had less lymph node (LN) recurrences distal to the common iliac bifurcation (35.2 vs. 57.9%, p = 0.05), but were more likely to harbor positive LNs proximal to the iliac bifurcation and in the presacral (34.2 vs. 12.3%, p = 0.002) areas as well as bone metastases (25.7 vs. 8.8%, p = 0.01). In the patient-based analysis, the patients with postoperative RT after RP had less recurrence in the pelvis only (pelvic LNs and/or prostate bed) (52.4 vs. 79%, p = 0.002), but were more likely to harbor extrapelvic recurrence (41.9 vs. 15.8%, p = 0.001). Patients who received RT to the prostate bed only had more recurrence to the pelvic LN only (54.2% vs. 23.4%, p = 0.002), but less extrapelvic recurrence (31.3 vs. 53.2%, p = 0.03) and less bone recurrence (16.7 vs. 36.2%, p = 0.031) compared to those patients, who received RT to the prostate bed and pelvic nodes. CONCLUSIONS: Postoperative radiation treatment alters the recurrence pattern in BCR patients after RP. Further prospective studies are needed to establish a decision tree for optimal imaging/management according to previous treatments.
Keywords: prostatektomie; Neoplasm Recurrence, Local; Combined Modality Therapy; Prognosis; Gallium Radioisotopes; senioři; Aged; Male; Retrospective Studies; lidé; PET/CT; izotopy gallia; Humans; Prostatectomy; retrospektivní studie; radiofarmaka; Radiotherapy; Austria; radioizotopy galia; Rakousko; radioterapie; Prostatic Neoplasms; lokální recidiva nádoru; mužské pohlaví; nádory prostaty; následné studie; Radiopharmaceuticals; kombinovaná terapie; Follow-Up Studies; prognóza; Positron Emission Tomography Computed Tomography; Gallium Isotopes